Clinical Needs as a Starting Point for Different Strategies in Computational Drug Development - Portela, César (Drug Research, 2019)
Traditionally, the first step in the development of drugs is the definition of the target, by choice of a biological structure involved in a disease or by recognition of a molecule with some degree of a biological activity that presents itself as druggable and endowed with therapeutic potential. The complexity of the pathophysiological mechanisms of disease and of the structures of the molecules involved creates several challenges in this drug discovery process. These difficulties also come from independent operation of the different parts involved in drug development, with little interaction between clinical practitioners, academic institutions and large pharmaceutical companies. Research in this area is purpose specific, performed by specialized researchers in each field, without major inputs from clinical practitioners on the relevance of such strategy for future therapies. Translational research can shift the way these relationships operate towards a process in which new therapies can be generated by linking experimental discoveries directly to unmet clinical needs. Computational chemistry methods provide valuable insights on experimental findings and pharmacological and pathophysiological mechanisms, allow the virtual construction of new possibilities for the synthesis of new molecular entities, and pave the way for informed cost-effective decisions on expensive research projects. This text focus on the current computational methods used in drug design, how they can be used in a translational research model that starts from clinical practice and research-based theorization by medical practitioners and moves to applied research in a computational chemistry setting, aiming the development of new drugs for clinical use.
Keywords: drug design; computational chemistry; clinical expertise; translational research